Starting Small: Building a Macroeconometric Model of the Philippine Economy - Margarita Debuque-Gonzales; John Paul P. Corpus (Philippine Institute for Development Studies (PIDS), 2022)
This study presents a small macroeconometric model of the Philippines. The model covers the basic parts of the economy-namely, private consumption and investment, international trade, employment, prices, and basic monetary sectors. Behavioral equations are estimated in errorcorrection form (using ARDL methodology) on quarterly data from 2002 to 2017. The model's validity is evaluated through various simulation exercises. It generates satisfactory in-sample and out-of-sample predictions for GDP growth, CPI inflation, and employment rate, but is less successful in tracking the movement of domestic interest rates. The model also shows plausible responses to exogenous shocks emanating from government consumption, world oil prices, and global GDP. Briefly, a government spending shock elicits increases in investment and imports, a shock to world oil prices generates faster inflation, while a global recession is transmitted to the domestic economy mainly through lower exports and investment. The next steps needed to extend the model beyond improving the existing blocks include developing the supply side, incorporating expectations, and adding fiscal and financial blocks.
Keywords: 330; macroeconometric model; Philippine economy; forecast; simulation